2021
DOI: 10.1371/journal.pone.0253863
|View full text |Cite
|
Sign up to set email alerts
|

Fatty infiltration in cervical flexors and extensors in patients with degenerative cervical myelopathy using a multi-muscle segmentation model

Abstract: Background In patients with degenerative cervical myelopathy (DCM) that have spinal cord compression and sensorimotor deficits, surgical decompression is often performed. However, there is heterogeneity in clinical presentation and post-surgical functional recovery. Objectives Primary: a) to assess differences in muscle fat infiltration (MFI) in patients with DCM versus controls, b) to assess association between MFI and clinical disability. Secondary: to assess association between MFI pre-surgery and post-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…A few studies have found that decreases in the FCSA/CSA of the MF and SSCa, which indicate increased fatty infiltration, were positively correlated with the preoperative mJOA 11,30 . However, Gu et al 18 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A few studies have found that decreases in the FCSA/CSA of the MF and SSCa, which indicate increased fatty infiltration, were positively correlated with the preoperative mJOA 11,30 . However, Gu et al 18 .…”
Section: Discussionmentioning
confidence: 96%
“…A few studies have found that decreases in the FCSA/CSA of the MF and SSCa, which indicate increased fatty infiltration, were positively correlated with the preoperative mJOA. 11,30 However, Gu et al 18 did not find a significant correlation between the morphology of the extensor muscle and the mJOA. Naghdi et al 17 proposed that the degree of the FCSA/CSA asymmetry was positively correlated with the mJOA at the level of the heaviest spinal cord compression and below.…”
Section: Paravertebral Muscle Correlationmentioning
confidence: 97%
“…Consequently, CPM investigation cannot be limited to fat infiltration, and further studies focusing on CSA of CPM are required to analyze its relevance with outcomes following HS or CDA. With the continuous progression of artificial intelligence, quantification of MRI based metric of muscle composition will contribute to analyses of CSA and FI in all paraspinal muscles ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our measures of multifidus fat infiltration were similar to those documented in whiplash-associated disorders (17–29.8%) [ 28 , 31 ] and in patients prior to cervical spine decompression surgery (31.7%) [ 25 ]. Fat infiltration in the cervical multifidus muscle has been well documented, notably in persons with whiplash-associated disorders who had poor recovery after injury and higher disability [ 26 , 28 , 31 , 48 ], as well as in patients with degenerative cervical myelopathy with poor functional recovery after surgery [ 30 ]. While the findings of our study in patients with CINP concur with these observations, they contrast with the results of Elliott et al [ 17 ], who found that cervical multifidus fat infiltration at C5/6 in their cohort of patients with CINP was not significantly different from asymptomatic participants.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher fat infiltration has been demonstrated in the multifidus of patients with degenerative cervical myelopathy [ 25 ] and with recalcitrant whiplash-associated disorders [ 26 ]. Fatty infiltration has been associated with poor outcomes (on the basis of the Neck Disability Index) for patients with whiplash-associated disorders [ 28 , 29 ], as well as with poor functional recovery after surgery among people with cervical degenerative myelopathy [ 30 ]. Patients with whiplash-associated disorders with severe disability had 45% greater fat infiltration compared to those with mild to moderate disability [ 31 ].…”
Section: Introductionmentioning
confidence: 99%